2011
DOI: 10.1371/journal.pone.0025395
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors of the Candida albicans Budded-to-Hyphal Transition Act through Multiple Signaling Pathways

Abstract: The ability of the pathogenic yeast Candida albicans to interconvert between budded and hyphal growth states, herein termed the budded-to-hyphal transition (BHT), is important for C. albicans development and virulence. The BHT is under the control of multiple cell signaling pathways that respond to external stimuli, including nutrient availability, high temperature, and pH. Previous studies identified 21 small molecules that could inhibit the C. albicans BHT in response to carbon limitation in Spider media. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 62 publications
(61 reference statements)
0
42
0
Order By: Relevance
“…4E) and mediated by a complex transcriptional network (8,24). In addition to nutrient-poor Spider media, mammalian serum also induces hyphae (25,26), and we observed that filastatin inhibited the response to both these stimuli (Fig. 3B).…”
Section: Filastatin Inhibits Hyphal Morphogenesis and Colony Morphologymentioning
confidence: 63%
See 3 more Smart Citations
“…4E) and mediated by a complex transcriptional network (8,24). In addition to nutrient-poor Spider media, mammalian serum also induces hyphae (25,26), and we observed that filastatin inhibited the response to both these stimuli (Fig. 3B).…”
Section: Filastatin Inhibits Hyphal Morphogenesis and Colony Morphologymentioning
confidence: 63%
“…4E). Cells constitutively overexpressing the G protein-coupled receptor Gpr1 become hyperfilamentous on solid Spider media by PKA stimulation (26,28), and we observed that filastatin blocked hyphal morphogenesis in these cells (Fig. 4A).…”
Section: Filastatin Inhibits Induction Of Hyphal Morphogenesis By Mulmentioning
confidence: 72%
See 2 more Smart Citations
“…Inhibition of the bud-to-hypha transition: The spider medium, N-acetylglucosamine (GlcNAc) medium, and Lee's medium were used for hyphal induction (10,11). C. albicans cells (10 6 mL) were added to each medium together with final concentrations 10 μg mL of each test compound, in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%